Strategi Pembelajaran dalam Mengatasi Kesulitan Belajar Online Anak Usia Dini - Khairunnisa Ulfadhilah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2021)
COVID-19 has an impact on all levels of education in Indonesia and has a major impact on early childhood, where the teaching and learning process needs to be done face-to-face, but due to the COVID-19 outbreak, the government's policy of face-to-face learning and online learning is carried out. Researchers conducting this research are interested in the learning strategies used by educators during the COVID-19 pandemic so that they can become a reference for parents in guiding children to learn online. The effect of learning for early childhood is difficulty in understanding explanations from educators, lack of socialization in children's lives because schools are held online, children's development and growth has decreased, children's achievement indicators will decrease. Online learning for children aged during this pandemic is not optimal because it has obstacles, namely COVID-19, which is the reason children experience the impact of learning at home. The research method used qualitative research to describe the findings in the field and then processed the data. The data collection techniques in the research that have been carried out are observation, interviews, and documentation. The results of this research are so that parents can guide, supervise and become a place for children's education in the family. Parents have a very big responsibility in educating and guiding children's learning online, the success of children's learning will be determined by parents if parents provide stimulation or guide when learning online.